2001
DOI: 10.1088/0953-8984/14/1/102
|View full text |Cite
|
Sign up to set email alerts
|

The high-temperature superionic behaviour of Ag2S

Abstract: Powder neutron diffraction and molecular dynamics (MD) simulations have been used to investigate the structural behaviour of silver sulfide, Ag2S, at elevated temperatures. Above ~450 K Ag2S adopts the β phase in which the S2- possess a body-centred cubic arrangement. Analysis of the neutron diffraction is in good agreement with the previously proposed structural model in which the Ag+ predominantly reside within the tetrahedral interstices. At ~865 K Ag2S transforms to the α phase in which the anion s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 26 publications
2
52
0
Order By: Relevance
“…Therefore, we conclude that model 5 (cations are distributed over ideal tetrahedral 8(c) and ideal octahedral 4(b) sites) describes fcc-Ag 3 CuS 2 in the optimal way (see the quality of the simultaneous fit in the figure 2). The same structural model was recently reported for superionic fcc-Ag 2 S [15] and fcc-(AgI) x -(PbI 2 ) 1-x with x= 5 4 and 3 2 [17]. In order to investigate the high-temperature behaviour of superionic fcc-Ag 3 CuS 2 , we analyzed synchrotron diffraction data in the temperature range from 543 K up to sample's melting on the basis of the model with random occupation of the tetrahedral 8(c) site at ( 4 1 , 4 1 , 4 1 ) and the octahedral 4(b) site at ( 2 1 , 2 1 , 2 1 ).…”
Section: Bcc-ag 3 Cussupporting
confidence: 64%
See 1 more Smart Citation
“…Therefore, we conclude that model 5 (cations are distributed over ideal tetrahedral 8(c) and ideal octahedral 4(b) sites) describes fcc-Ag 3 CuS 2 in the optimal way (see the quality of the simultaneous fit in the figure 2). The same structural model was recently reported for superionic fcc-Ag 2 S [15] and fcc-(AgI) x -(PbI 2 ) 1-x with x= 5 4 and 3 2 [17]. In order to investigate the high-temperature behaviour of superionic fcc-Ag 3 CuS 2 , we analyzed synchrotron diffraction data in the temperature range from 543 K up to sample's melting on the basis of the model with random occupation of the tetrahedral 8(c) site at ( 4 1 , 4 1 , 4 1 ) and the octahedral 4(b) site at ( 2 1 , 2 1 , 2 1 ).…”
Section: Bcc-ag 3 Cussupporting
confidence: 64%
“…The analysis of the diffraction check-pattern from the sample after the heat treatment in argon during the diffraction measurements shows no changes with respect to the initial state. The systematics of the phase transitions of related copper-and silver-based superionics was considered by Hull et al [15], where the disordered fcc structure (or related hcp structure) was suggested to be always the lower temperature modification, with the bcc -AgI-like structure occurring at the highest temperature. Despite this assumption, the fcc structure was found to be the high temperature phase for Ag 2 S in a reference [15] which was stated to be anomalous.…”
Section: Structural Aspects Of Ag 3 Cus 2 In Superionic Statementioning
confidence: 99%
“…Based on these observations, they attributed the (√7×√7)R19° pattern to the formation of an epitaxial film of the high temperature phase of Ag 2 S (referred to as the γ-phase in the very limited report of its structure [6]). This bulk structural phase of Ag 2 S has been characterised more fully by neutron scattering [7 ] and confirmed to have a facecentred cubic lattice with a lattice parameter of 6.27 Å. As such the S-S spacing in the (111) plane is 4.43 Å, an almost perfect match to the √(7/3) spacing 4.41 Å required for epitaxial growth on Ag(111) with a (√7×√7)R19° registry mesh.…”
Section: N Mmentioning
confidence: 77%
“…[11][12][13] It has significant applications in optical and electronic devices such as photoconductors, photovoltaic cells, and superionic conductors. [14][15][16] Single-crystalline Ag 2 S nanowires can be expected to have superior properties owing to their anisotropic geometry, large surface-to-volume ratio, and carrier and photon confinement in two dimensions. However, because the synthesis of Ag 2 S nanowires with high aspect ratios, good quality, and high yield is a great challenge, nanodevices based on Ag 2 S semiconductor nanowires are limited.…”
mentioning
confidence: 99%